2023
DOI: 10.1101/2023.04.06.535361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Embryo-specific epigenetic mechanisms reconstitute the CHH methylation landscape during Arabidopsis embryogenesis

Abstract: The modification of flowering plant DNA by CHH methylation acts primarily to silence transposable elements, of which many active copies are present in Arabidopsis thaliana. During embryogenesis, the CHH methylation landscape is dramatically reprogrammed, resulting in exceedingly high levels of this modification upon mature embryo formation. The mechanisms constituting the remodeling process, and its function in embryos, are unclear. Here, we isolate embryos from Arabidopsis plants harboring mutations for key c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 46 publications
(103 reference statements)
1
11
0
Order By: Relevance
“…In addition, when we mapped the position of these non-sRNA overlapping CHH methylated regions, we found that they were tightly centromeric, and as such likely to be conferred by CMT2 ( Supplementary Figure S1 ). To further investigate the positive correlation of CHH methylation spreading with sRNA clusters, we visualized individual overlapping loci, and observed that expanding sRNA expression was coincident with CHH methylation spreading and accumulation ( Figures 2D–F ), providing support for previous observations that increased embryo CHH methylation is conferred by the RdDM pathway ( Hsieh et al., 2023 ).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…In addition, when we mapped the position of these non-sRNA overlapping CHH methylated regions, we found that they were tightly centromeric, and as such likely to be conferred by CMT2 ( Supplementary Figure S1 ). To further investigate the positive correlation of CHH methylation spreading with sRNA clusters, we visualized individual overlapping loci, and observed that expanding sRNA expression was coincident with CHH methylation spreading and accumulation ( Figures 2D–F ), providing support for previous observations that increased embryo CHH methylation is conferred by the RdDM pathway ( Hsieh et al., 2023 ).…”
Section: Resultssupporting
confidence: 79%
“…RdDM targets are methylated by de novo methyltransferases, DRM1 and 2. Recent papers described the delineation of embryo CHH loci into classes based on their mechanism of catalysis using drm1/2 and cmt2 mutants ( Kawakatsu et al., 2017 ; Hsieh et al., 2023 ). Briefly, if an embryonic CHH DMR is targeted by CMT2 both in the vegetative (leaves) and reproductive embryo stages, that DMR is denoted as a conserved CMT2 (cCMT2) DMR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations